Pemanfaatan E-Commerce Shopee dalam Meningkatkan Strategi Pemasaran Usaha Mikro Kecil dan Menengah (UMKM) di Kecamatan Cimanggis Kota Depok - Rizki Plasnajaya; Aghnia Wulandari; Pramuda Octabudiaji; Awaludin; Rizal Ardiansyah; Defi Rizka Rahmawati; Balqis Ummiyamarroh; Uli Marsella (Jurnal Pengabdian Masyarakat Program Pemberdayaan Masyarakat Nasional, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the global economy, contributing significantly to employment and economic growth. In today's digital age, it is essential for MSMEs to utilize E-Commerce platforms like shopee to reach a wider customer base and expand their businesses beyond traditional brick-and-mortar stores. By tapping into the online marketplace, MSMEs can increase their visibility, attract new customers, and ultimately drive sales and revenue growth. The convenience and accessibility of e-commerce platforms make it easier for MSMEs to compete with larger retailers and establish a strong online presence.Keyword : MSMEs, economic growth, digital age, Expanding Business, attract new customers.